2013
DOI: 10.1007/s10029-013-1102-y
|View full text |Cite
|
Sign up to set email alerts
|

Modified fixation free plug technique using a new 3D multilamellar implant for inguinal hernia repair

Abstract: The results of this retrospective study on a new method of inguinal hernia repair using a three dimensional handcrafted multilamellar implant delivered with a modified placement technique are promising. The short-, medium- and long-term complications were notably low. No recurrences were noticed but, more importantly, no chronic pain and extremely low discomfort rates were observed even in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…Recovery is excellent even with bilateral repair or some fixation [7] . In our study, no postoperative adverse event was reported in any patient in either of the 2 groups; like that observed by Amato G and colleagues [8,9] . In the present study, recurrence was noted in 1 (1.33%) patient in the conventional group, while there was no recurrence among the patients treated with the 3D mesh.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Recovery is excellent even with bilateral repair or some fixation [7] . In our study, no postoperative adverse event was reported in any patient in either of the 2 groups; like that observed by Amato G and colleagues [8,9] . In the present study, recurrence was noted in 1 (1.33%) patient in the conventional group, while there was no recurrence among the patients treated with the 3D mesh.…”
Section: Discussionsupporting
confidence: 91%
“…Paliwal et al reported no recurrence among any of their 260 study patients. 11 Amato G et al also reported no recurrence in both their studies [8,9] . In our study, the mean ± SD hospital stay was higher (3.27 ± 0.91 days) in the conventional group as compared to the 3D mesh group (1.83 ± 0.53 days).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In some studies, lower rates of both complications and pain have been reported to develop following MPR [ 11 , 13 ]. In contrast, the complication rate was reported to be higher especially due to migration of the mesh [ 4 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Especially for soft tissue engineering, the dilemma is balanced between on one hand, having a lightweight mesh, but on the other hand offering a 3‐D macroporous structure that facilitates muscle regeneration. Encouraging results using 3‐D multi‐lamellar plugs made of PP aimed at filling hernia defects and 3‐D non‐woven macroporous scaffolds made of PVDF were recently published and different companies are already offering similar products (e.g., ProFlor by Insightra Medical, Prolene 3D by Covidien and 3DMax Mesh by Bard) . Nevertheless, an important requirement to keep in mind is the ability to deliver the 3‐D scaffold into the abdominal cavity using minimal invasive surgery, facilitated by the self‐fixation property exhibited by some of the listed 3‐D implants with dynamic memory shape characteristics …”
Section: Perspectives In Mesh Evolutionmentioning
confidence: 99%